DIATHESIS MARKERS IN WOLIONESE LANGUAGE (PEMARKAH DIATESIS DALAM BAHASA WOLIO) - Nuz Chairul Mugrib; Dian Wahyunianto; Sumarlam Sumarlam (Leksema: Jurnal Bahasa dan Sastra, 2018)
Wolionese language is the language spoken by the people in Bau-Bau, Southeast Sulawesi. The objective of this study is to describe active-passive voice of Wolionese that has not been widely studied. This study applied descriptive qualitative approachusing basic method, direct constituent division and advanced method form changing. The data were obtained by using cooperative method. The change of active sentence structure into passive sentence in Wolionese has its own pattern. Based on the data analysis of the active-passive voice of Wolionese, the result shows that Wolionese has specific markers attached in the verbs of the sentences to form or change from active voice to passive voice and vice versa. In the active voice, the markers found are ku-, ta-, u-, and a- that always be attached in the beginning of the verbs. They sometimes are also followed by -aka, -mo attached in the end of the verb. Meanwhile, in the passive voice there are also several markers found, they are -a, to- and i- that are attached in the end of the verb (-a) and in the beginning of the verb (to- and i-).